2022
DOI: 10.22270/jddt.v12i1.5266
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Antipsychotic Drug Use and Liver Enzyme Levels in People with Mental Disorders

Abstract: The long-term use of some drugs causes side effects in the form of elevated liver enzyme levels. Meanwhile, antipsychotic drug therapy in people with mental disorders induces liver injury which leads to an elevation in serum glutamic oxaloacetic and pyruvic transaminases. Therefore, this study aims to analyze the relationship between the uses of antipsychotic drugs with elevated liver enzymes in people with mental disorders. This observational study used a cross-sectional design that included 69 people with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This gender disparity may be due to the antidopaminergic effect of estrogen in women, as the hormone estrogen has been shown to inhibit the release of dopamine in the nucleus accumbens. It has been suggested that the cause of schizophrenia is an increase in the number of dopamine receptors in the caudate nucleus, nucleus accumbens, and putamen and that the estrogen neuroprotective role may be responsible for the reduced incidence and improved course of the disease in women (Canuso and Pandina, 2007; Meiyanti et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This gender disparity may be due to the antidopaminergic effect of estrogen in women, as the hormone estrogen has been shown to inhibit the release of dopamine in the nucleus accumbens. It has been suggested that the cause of schizophrenia is an increase in the number of dopamine receptors in the caudate nucleus, nucleus accumbens, and putamen and that the estrogen neuroprotective role may be responsible for the reduced incidence and improved course of the disease in women (Canuso and Pandina, 2007; Meiyanti et al , 2022).…”
Section: Discussionmentioning
confidence: 99%